2021
DOI: 10.3892/etm.2021.10874
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA RP11‑531A24.3 inhibits the migration and proliferation of vascular smooth muscle cells by downregulating ANXA2 expression

Abstract: A complete understanding of the behavioral influence and phenotypic transition of vascular smooth muscle cells, as well as the effects of the characteristics of these cells on the physiological and pathological processes of atherosclerosis, is crucial if new therapeutic targets for atherosclerosis are to be identified. In the present study, the long non-coding RNA RP11-531A24.3 was identified to be expressed at low levels in plaque tissues through screening a microarray for differentially expressed genes. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…LncRNA BANCR overexpression induces HASMC proliferation by downregulating miR-34c methylation and reversing the effect of miR-34c on HMGB1, TNF-α, and Bcl-2 expression, thereby promoting HASMCs proliferation and inhibiting apoptosis (30). The expression of LncRNA RP11-531A24.3 is reduced in advanced AS lesions; in cells overexpressing it, lncRNA RP11-531A24.3 inhibits the migration and proliferation of HA-VSMCs by binding directly to the RNA-binding protein annexin 2 (ANXA2) in the cytoplasm to reduce its expression at the mRNA and protein levels (31).…”
Section: Lncrna and Atherosclerosismentioning
confidence: 99%
“…LncRNA BANCR overexpression induces HASMC proliferation by downregulating miR-34c methylation and reversing the effect of miR-34c on HMGB1, TNF-α, and Bcl-2 expression, thereby promoting HASMCs proliferation and inhibiting apoptosis (30). The expression of LncRNA RP11-531A24.3 is reduced in advanced AS lesions; in cells overexpressing it, lncRNA RP11-531A24.3 inhibits the migration and proliferation of HA-VSMCs by binding directly to the RNA-binding protein annexin 2 (ANXA2) in the cytoplasm to reduce its expression at the mRNA and protein levels (31).…”
Section: Lncrna and Atherosclerosismentioning
confidence: 99%
“…LncRNA RP11-531A24.3 is down-regulated in atherosclerotic plaque tissues. Yilin Wu et al [31]found that LncRNA rp11-531a24.3 plays a role in inhibiting theproliferation and migration of VSMCs by inhibiting the expression of ANXA2 mRNA and protein levels.ANXA2, a member of the calcium-dependent phospholipid-binding protein family, enhances proliferation and migration in various cancers and is associated with smooth muscle contraction [32].…”
Section: Lncrna 430945mentioning
confidence: 99%